Analysis of Three Dimensional Aspects of the Main Character in Frances Ha Film - Hardiyanti, Ayu Fitri; Jayantini, I Gusti Agung Sri Rwa; Juniartha, I Wayan (Journal of Language and Applied Linguistics, 2024)
In literary works such as short stories, novels, dramas, and films, the characters in the film play a very important role in conveying the story. Having a character with a strong personality can make a good impression on the audience and readers. In this case, the role of the author is very important in creating characters that have strong personalities through character development so that they can create a realistic character. This study aims to determine how the author portrays the main character, Frances Halladay, in terms of three dimensions of characterization, by using the character dimensions theory of Egri (1960). This research uses descriptive qualitative research methods, and the object of study is the film Frances Ha, which was released in 2012 and directed by Noah Baumbach. Observation and documentation methods were used in this study by watching the film, reading the script, and taking notes. The results of the research can be concluded that the main character, Frances Halladay, in the film Frances Ha, shows three dimensions of characterization possessed by the main character, namely physiological, psychological, and sociological. In presenting this dimension, this study presents figures and/or dialogue from the film.